Flavonoid supplements increase neurotrophin activity to modulate inflammation in retinal genetic diseases - Kiani, Aysha Karim; Falsini, Benedetto; Ziccardi, Lucia; Gusson, Elena; Mangialavori, Domenica; Allegrini, Francesca; Colao, Emma; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Retinal degenerative disorders induce loss of photoreceptors associated with inflammation, and negative remodeling and plasticity of neural retina. Retinal degenerative diseases may have genetic and/or environmental causes. Degeneration of retinal pigment epithelium cells initiates a vicious circle increasing the ongoing inflammation in both retina and choroid. Flavonoids are polyphenolic molecules with antioxidant activity and dietary intake, specifically of anthocyanins and flavanols, improves oxidative stress and neuro-inflammation. In vitro and ex vivo studies have also revealed biological effects of flavonoids on retinal protection against oxidative stress and inflammation. In this brief review, the protective role of flavonoids against retinal degeneration and inflammation will be discussed along with their therapeutic potential for the treatment of retinal degenerative diseases.